10. Interpretative Performances: Elisabeth Leonskaya And Paul Badura-Skoda - Tudor Brînduşa (Sciendo, 2018)
In the complex road of deciphering and understanding a musical work, an important step for the pianist (performer or professor) is represented by the choice of reference interpretations according to some famous musicians. Elisabeth Leonskaya and Paul Badura - Skoda are among the most distinguished representatives of the contemporary school of piano.